(3LghO QTjO CMeO Gdcfchgj (B((3J(B:1323 (3g`(B) (3aj Gdabg GdESdGej (B/ s - (3eMeO gGQhf GdQTjO Hf eMeO YHOGddWjas; (3MSjf CMeO YHOGdZfj SeQI (B: s ((3GdbGgQI (B: s (3eMeO gGQhf GdQTjO Hf eMeO YHOGddWja (B: s, 2013)
(3JgOa GdQSGdI Edi GdJYQja HGdTjN QTjO CMeO Gdcfchgj (B- (3QMeg Gddg (B- (3h EHQGR LghOg aj Gdabg h CUhdg (B: (3aJfGhdJ GdOQGSI LhGfH TNUjI Gdcfchgj h JCKQg h JCKjQg aj YUQg (B: (3ceG CHQRJ LghO Gdcfchgj aj GdCOdI GdCUhdjI h GdbhGYO GdabgjI eY HjGf ehbag ef GdGSJOdGd HGdbQBf (B: (3h GdSfI (B: (3h GdELeGY (B: (3h GdbjGS (B: (3h bhd GdUMGHj (B: (3h GdYQa (B: (3h GdGSJMSGf (B: (3HPcQ GdeSGFd GdJWHjbjI ajgG(B. (3h ceG CXgQJ GdOQGSI edcI Gdcfchgj GdabgjI h ecGfJg GdYdejI aj GdePgH GdMfaj h JQLjMg h EdJRGeg HPdc aj GdLedI (B: (3EdG Cfg cGf eYJOdB ajg (B: (3MjK dG jQLM GdePgH GdMfaj Ohf Odjd(B: (3h jJVM Pdc aj GdfeGPL GdePchQI ajgG ef GNJjGQGJg GdabgjI h GdCUhdjIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdTQjYI GdGSdGejI s
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdMjGIs; (3Gdabgs; (3LghO Gdcfchgjs